2017
DOI: 10.1016/j.scitotenv.2017.01.207
|View full text |Cite
|
Sign up to set email alerts
|

Environmental life cycle assessment of producing willow, alfalfa and straw from spring barley as feedstocks for bioenergy or biorefinery systems

Abstract: The current study aimed at evaluating potential environmental impacts for the production of willow, alfalfa and straw from spring barley as feedstocks for bioenergy or biorefinery systems. A method of Life Cycle Assessment was used to evaluate based on the following impact categories: Global Warming Potential (GWP), Eutrophication Potential (EP), Non-Renewable Energy (NRE) use, Agricultural Land Occupation (ALO), Potential Freshwater Ecotoxicity (PFWTox) and Soil quality. With regard to the methods, soil organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 82 publications
(133 reference statements)
0
23
0
Order By: Relevance
“…Tonini et al (2016) reported that biofuel production from the agricultural residues without involving land use change is a promising emission reduction option from the perspective of life cycle. According to Parajuli et al (2017), cultivating willow and alfalfa as feedstocks for bioenergy can potentially sequestrate more soil organic carbon and thus lead to a lower carbon footprint. The bioenergy crops cultivation (e.g., Miscanthus) has also been regarded as the effective CO 2 sink in UK (McCalmont et al 2017b), indicating the bioenergy production can be a good choice for capturing more carbon in soil.…”
Section: Life Cycle Environmental Impact Assessment Of Bioenergy Prodmentioning
confidence: 99%
“…Tonini et al (2016) reported that biofuel production from the agricultural residues without involving land use change is a promising emission reduction option from the perspective of life cycle. According to Parajuli et al (2017), cultivating willow and alfalfa as feedstocks for bioenergy can potentially sequestrate more soil organic carbon and thus lead to a lower carbon footprint. The bioenergy crops cultivation (e.g., Miscanthus) has also been regarded as the effective CO 2 sink in UK (McCalmont et al 2017b), indicating the bioenergy production can be a good choice for capturing more carbon in soil.…”
Section: Life Cycle Environmental Impact Assessment Of Bioenergy Prodmentioning
confidence: 99%
“…Many cases involving the assessment of impact on ecosystem services used soil-quality-related indicators (e.g., soil organic carbon and erosion) [44][45][46][47][48][49][50][51][52]. This reveals that assessed items are still limited when compared with the assessment of diverse agriculture-related ecosystem services (Table 1).…”
Section: Results and Insights From Survey (1)mentioning
confidence: 99%
“…Soil carbon sequestration was adopted at 9.7% of the net C input [28]. The net C input was calculated from the difference between the amount of organic matter (OM) available to giant miscanthus (digestate and crop residues) and spring barley (cultivated in a conventional tillage system) with straw incorporated into the soil (as reference) [29,30]. The number of crop residues introduced to soil was calculated in the C-TOOL model [31].…”
Section: Modelling and Data Sourcesmentioning
confidence: 99%